Changes in the ankle-brachial blood pressure index among hemodialysis patients. Issue 1 (December 2016) - Abe, Takayuki; Otsubo, Shigeru; Kimata, Naoki; Okajima, Tomoki; Otani, Yumi; Murakami, Jun; Kaneko, Iwakazu; Miwa, Naoko; Mineshima, Michio; Tsuchiya, Ken; Nitta, Kosaku; Akiba, Takashi
Abstract Background The ankle-brachial blood pressure index (ABI) is an independent predictor of mortality in hemodialysis patients. In the present study, we investigated the factors that predict changes in the ABI in hemodialysis patients. Methods A total of 61 consecutive patients receiving maintenance hemodialysis who successfully underwent ABI examinations in 2005 and 2011 were enrolled in this study. The change in the ABI (2011 measurement versus 2005 measurement) was estimated. We set the baseline at 2011 and investigated the patient outcomes. Furthermore, we compared the change in the ABI and several clinical factors observed in 2005. Results The mean follow-up period was 3.1 ± 0.7 years. In the univariate Cox proportional hazard analysis, predictive variables for mortality included ABI (0.43 [0.25–0.64]; [per 0.1 increase]) and the change in the ABI (0.62 [0.49–0.79]; [per 0.1 increase]). Patient age was negatively correlated and the serum creatinine level was positively correlated with the change in the ABI (P = 0.030 and 0.022, respectively). Conclusions We confirmed that not only the value of the ABI itself but also the change in the ABI was a risk factor for mortality among hemodialysis patients. The change in the ABI was negatively correlated with age and was positively correlated with the serum creatinine level. Careful observation of the ABI is needed for old patients and patients with a low serum creatinine level.